2007
DOI: 10.1080/00036840500486516
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in unemployment: empirical evidence from Taiwan's region data based on panel unit root tests

Abstract: In this study, we test the hysteresis hypothesis in unemployment for Taiwan's 21 regional data sets using the Levin et al. (2002), Im et al. (2003) and Taylor and Sarno (1998) panel-based unit root tests for the June 1993 to September 2001 period. The results from all three tests provide evidence that based on Taiwan's regional unemployment data the hysteresis hypothesis can justifiably be rejected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…We obtained overwhelming evidence against the null hypothesis of a unit root and, therefore, concluded that all variables were stationary. The results are in accordance with Chang et al (2007).…”
Section: Methodssupporting
confidence: 90%
“…We obtained overwhelming evidence against the null hypothesis of a unit root and, therefore, concluded that all variables were stationary. The results are in accordance with Chang et al (2007).…”
Section: Methodssupporting
confidence: 90%
“…On the contrary, Smyth (2003) both used the LLC and the IPS PUR tests from the 1983Q2 to 2002Q1 in states of Australia and he concluded that the hysteresis hypothesis was valid. Chang et al (2007) used the LLC, the IPS and Taylor and Sarno (1998) 's PUR tests from 1993M7 to 2001M9 in 21 regions of Taiwan, and they concluded that the hysteresis hypothesis was rejected by all PUR tests. Gomes and Da Silva (2009) applied the unit root test by Lee and Strazicich (2003) from 1981M1 to 2002M12 in 6 major Brazilian metropolitan-areas and the result of unit root tests showed that the hysteresis hypothesis was only rejected in one region.…”
Section: Introductionmentioning
confidence: 99%
“…In the countries of Asian and Africa, the empirical evidence reported is also diverse (Chang, et al, 2007;Lee, Wu and Lin, 2010;Eisazadeh and Tabarsi, 2013;Furuoka, 2014a;Pikoko and Phiri, 2019;Yaya, Ogbonna and Mudida 2019). Chang et al (2007) found no evidence of UHH in all the 21 regions of Taiwan. The results documented by Lee, Wu and Lin (2010) showed that there exists UHH in all the East-Asian countries considered including Taiwan.…”
Section: Literature Reviewmentioning
confidence: 99%